STRUCTURAL CHANGES IN THE SMALL INTESTINE WALL AT THE MECHANICAL OBSTRUCTION OF THE DIGESTIVE CHANNEL IN THE EXPERIMENT - Dzyubanovskyi, I.Ya.; Benedykt, V.V.; Nesteruk, S.O.; Volkov, K.S. (World of Medicine and Biology, 2019)
Detailed histological and electron microscopic studies of structural components of the small intestine wall in laboratory white rats have been performed with simulated acute intestinal obstruction. The violations of the vascular bed of the muscle and submucosal membranes are described, and significant destruction of myocytes and histological changes of the structures of the mucous membrane of the small intestine during experimental intestinal obstruction. Attention is drawn to the need to take into account the revealed pathological changes in the obstruction of a small intestine in clinical conditions in order to correct them.
Keywords: small intestine; acute mechanical obstruction; histological and electron microscopic studies; white rats